2007
DOI: 10.4055/jkoa.2007.42.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Preoperative Degeneration of the Adjacent Segment after Instrumented Lumbar Arthrodesis

Abstract: ,7,9,11,12,17,22,23) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Gillet 8) reported that segments with degenerative changes before surgery did not play a significant role in terms of long-term results, and thus, performed fusion surgery only on segments related to current symptoms. On the contrary, there have been reports that degenerative changes in adjacent segments after surgery were accelerated after initial fusion and increased the prevalence of adjacent segment disease 3,6,9,35) . We measured preoperative segmental angles of upper and lower lumbar vertebrae adjacent to segments at which ASD occurred after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gillet 8) reported that segments with degenerative changes before surgery did not play a significant role in terms of long-term results, and thus, performed fusion surgery only on segments related to current symptoms. On the contrary, there have been reports that degenerative changes in adjacent segments after surgery were accelerated after initial fusion and increased the prevalence of adjacent segment disease 3,6,9,35) . We measured preoperative segmental angles of upper and lower lumbar vertebrae adjacent to segments at which ASD occurred after surgery.…”
Section: Discussionmentioning
confidence: 99%